Differential charge-transfer cross sections for systems with energetically degenerate or near-degenerate channels - Nguyen, H.; Brédy, R.; Camp, H. A.; Awata, T.; DePaola, B. D. (My University, 2004)
Resolution plays a vital role in spectroscopic studies. In the usual recoil-ion momentum spectroscopy (RIMS), Q-value resolution is relied upon to distinguish between different collision channels: The better the Q-value resolution, the better one is able to resolve energetically similar channels. Although traditional COLTRIMS greatly improves Q-value resolution by cooling the target and thus greatly reducing the initial target momentum spread, the resolution of the technique is still limited by target temperature. However, with the recent development in RIMS, namely, magneto-optical trap recoil ion momentum spectroscopy (MOTRIMS) superior recoil ion momentum resolution as well as charge transfer measurements with laser excited targets have become possible. Through MOTRIMS, methods for the measurements of target excited state fraction and kinematically complete relative charge transfer cross sections have been developed, even for some systems having energetically degenerate or nearly degenerate channels. In the present work, the systems of interest having energy degeneracies or near degeneracies are Rb+, K+, and Li+ colliding with trapped Rb(5l), where l=s and p.